Colon mucosa of patients both with spondyloarthritis and Crohn's disease is enriched with macrophages expressing the scavenger receptor CD163. Issue 2 (27th May 2004) - Demetter, P; De Vos, M; Van Huysse, J A; Baeten, D; Ferdinande, L; Peeters, H; Mielants, H; Veys, E M; De Keyser, F; Cuvelier, C A
Abstract : Background: Crohn's disease is associated with an increased number of macrophages in ileal and colonic mucosa. Data on macrophages in gut mucosa of patients with spondyloarthritis (SpA) are scarce. Objective: To investigate macrophages and other antigen presenting cells in gut mucosa from patients with SpA and Crohn's disease, given the relationship between both entities. Methods: Biopsy specimens from patients with SpA, Crohn's disease, ulcerative colitis, and from controls were immunohistochemically stained with different markers for macrophages and dendritic cells. Slides were scored semiquantitatively on a four point scale. Results: SpA and Crohn's disease were associated with large numbers of CD68 + macrophages. Colon mucosa of both patients with SpA and Crohn's disease, but not ulcerative colitis, showed increased numbers of macrophages expressing the scavenger receptor CD163. Conclusions: Macrophages expressing the scavenger receptor CD163 are increased in colonic mucosa in SpA and in Crohn's disease, highlighting the relationship between these entities. The increased number of CD163 + macrophages in colon mucosa of patients with SpA suggests this is another argument for a role of macrophage scavenger receptors in this group of diseases.